Vitamin E and cancer prevention. - Knekt, P; Aromaa, A; Maatela, J; Aaran, R; Nikkari, T; Hakama, M; Hakulinen, T; Peto, R; Teppo, L (1991)
Some animal experiments and human studies suggest that vitamin E may protect against cancer. Serum alpha-tocopherol concentration was studied for its prediction of cancer in a cohort of 36,265 adults in Finland. During a mean follow-up of 8 y, cancer was diagnosed in 766 persons. The levels of serum alpha-tocopherol were determined from stored serum samples (at -20 degrees C) taken from these cancer patients and from 1419 matched control subjects. Individuals with a low level of alpha-tocopherol had about a 1.5-fold risk of cancer compared with those with a higher level. The strength of the association between serum alpha-tocopherol level and cancer risk varied for different cancer sites and was strongest for some gastrointestinal cancers and for the combined group of cancers unrelated to smoking. The association was strongest among nonsmoking men and among women with low levels of serum selenium. The findings agree with the hypothesis that dietary vitamin E in some circumstances protects against cancer.